Schutz vor Über- und Unterversorgung – Einführung in die DEGAM-Leitlinie - Kühlein, Thomas; Egidi, Günther; Scherer, Martin; Wagner, Hans Otto; Dubben, Hans Hermann; Lühmann, Dagmar; Abiry, Dorit; Barzel, Anne; Muche-Borowski, Cathleen (Zeitschrift für Allgemeinmedizin, 2023)
Background: In June 2019, a new guideline by the German College of General Practitioners and Family Physicians (DEGAM) “Protection of medical overuse and underuse – deciding together” was published. This article echos the introduction of the guideline in a more compact and revised form. Objectives: To raise awareness of the problems of medical over- and underuse and of the existence of the guideline for a broader readership. Materials and methods: The basis of this article is the introduction and background of the guideline text, which has been revised and amended by the authors who are members of the guideline panel. Results: First medical over- and underuse are defined. Then the article introduces the reader to the causes, dimensions, and solutions of both phenomena. This includes the consequences of medical overuse for planetary health. Conclusion: Medical over- and underuse are frequent and relate to each other. The guideline offers, based on the recommendations of the other DEGAM guidelines as well as the German National Clinical Guidelines, a core set of recommendations to mitigate medical over- and underuse.
CRIS-Team Scopus Importer:2023-07-21
Keywords: General practice; Medical overuse; Overdiagnosis; Overtherapy; Planetary health